Annual Plan 1998-99 Volume-II Government of Karnataka - Planning Commission (Planning Commission, 1998)
GN Statement Annual Plan Outlay ScheMewise Details of Expenditure during the Annual Plan 1997-98 and outlay for Annual Plan 1998-99 Physical Targets and Achievement during the Annual Plan 1997-98 and Target for the Annual Plan 1998-99 Proposals for Spillover and Ongoing programmes/Project
Government of Karnataka